Application of Internet for Service Delivery in Selected Special Libraries in Kaduna Metropolis - Ikegwuiro, Patience Uloaku (European Scientific Journal, ESJ, 2017)
The study investigated the Application of Internet for service delivery in some selected special libraries in Kaduna state. The objectives of the study were to ascertain the kind of Internet services used in the special libraries; to ascertain the library services where internet is applied; to find out the extent of internet application in library services; to ascertain the level of satisfaction of the staff with the application of the Internet and to determine the factors that hinder the effective application of Internet in the libraries. Survey method of research was adopted. The population of the study was made up of 38 library staff from the four (4) selected special libraries. Descriptive statistical tools such as simple percentages and tables were used to analyze the data. The study revealed that the application of Internet to library services is not significantly high. The study also found out that the librarians derive satisfaction in the application of Internet in their library services because it helps for effective services delivery, though some factors were discovered to be a hindrance for effective application of the Internet in the special libraries which include: low bandwidth; poor funding; erratic power supply, technology obsolescence and high cost of connectivity and maintenance. The study recommends that Internet services should be adequately used by the special libraries in Kaduna metropolis in carrying out the housekeeping operations and services of the library; libraries administrations in Kaduna metropolis should make sure that there is steady power supply in the libraries for effective use of the Internet services for service delivery; The special libraries should make sure that Internet facilities are serviced regularly; and training of staff on for effective use of the Internet. The study concludes that special libraries in Kaduna metropolis are still on the verge of meeting up with the global perspective of ICT compliance. This notwithstanding, the Internet services are available in such a way that libraries can apply them to library service to enhance the quality of their service delivery.